Dimensão dignatária da Justiça Desportiva como instrumento de efetividade da dignidade da pessoa humana - Zanini, Flavia de Almeida de Oliveira (2023)
This thesis aims to present Sports Law as a fundamental right in the light of the 1988 Constitution of the Federative Republic of Brazil. In this sense, there is a need for a specialized Sports Justice, with its own jurisdiction and competence. The approach to the topic researched was born from the fact that there are, in professional sports, instances in the exercise of prerogatives similar to those of the Judiciary, that is, the autonomy for self-administration and judgment of demands, through a specific sports litigation, with forecast constitutional. Limiting the access of athletes and clubs to the Judiciary provokes discussions, even though the Brazilian legal system has adopted the single jurisdiction system, in which the conflicts, interests and disputes of society must be decided by the Judiciary. We confront the national sports legislation with the international sports legal systems, seeking to build hypotheses in order to safeguard fundamental rights, expanding the instruments for solving the demands, here judged by the Sports Justice, without, however, emptying or withdrawing the state competence of the Judiciary Power. To this end, it is necessary that the Brazilian sports system be restructured, institutionalizing the specific decision-making bodies, as well as expanding the means of resolving disputes, with the permanent integration of mediation, arbitration and conciliation, as provided by the sports legal system, including the art. 231 of the Brazilian Code of Sports Justice